2018
DOI: 10.1017/jfm.2018.79
|View full text |Cite
|
Sign up to set email alerts
|

Testing linear marginal stability in stratified shear layers

Abstract: We use two-dimensional direct numerical simulations of Boussinesq stratified shear layers to investigate the influence of the minimum gradient Richardson number $Ri_{m}$ on the early time evolution of Kelvin–Helmholtz instability to its saturated ‘billow’ state. Even when the diffusion of the background velocity and density distributions is counterbalanced by artificial body forces to maintain the initial profiles, in the limit as $Ri_{m}\rightarrow 1/4$, the perturbation growth rate tends to zero and the satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
1
16
3
Order By: Relevance
“…This apparent inconsistency between our results and the theoretical analysis of Howland et al. (2018) gives a clue to the mechanism underlying the ‘relaxation’ process that we have suggested occurs in the initial stages of the evolution of our flow. An important point of difference between conditions in the near-surface region of our equilibrium state flow and those in the analysis of Howland et al.…”
Section: Vertical Profilescontrasting
confidence: 99%
See 2 more Smart Citations
“…This apparent inconsistency between our results and the theoretical analysis of Howland et al. (2018) gives a clue to the mechanism underlying the ‘relaxation’ process that we have suggested occurs in the initial stages of the evolution of our flow. An important point of difference between conditions in the near-surface region of our equilibrium state flow and those in the analysis of Howland et al.…”
Section: Vertical Profilescontrasting
confidence: 99%
“…In the near-surface region the mean velocity and temperature profiles (see figure 6) contain an inflection and hence are similar to the canonical conditions under which Kelvin–Helmholtz and Holmboe instabilities form. Howland, Taylor & Caulfield (2018) investigated marginal stability associated with the formation of K–H waves from laminar initial conditions and showed the marginal stability limit to be . In fact Kaminski, Caulfield & Taylor (2017) have shown that Kelvin–Helmholtz-like billows can form for up to 0.4 in the presence of perturbations that are sufficiently large and that have the optimal structure for amplification.…”
Section: Vertical Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the vorticity structure of the steady states at two different values of Ri b . In the case of the Hopf bifurcation, billow-like structures are clearly seen, bearing a strong resemblance to the saturated, unsteady billows found by Howland et al (2018). Increasing Ri b along the upper branch to the saddle-node bifurcation, these structures remain but become significantly less pronounced.…”
Section: Uniform Stratification: the Drazin Modelmentioning
confidence: 69%
“…Miles (1961) and Howard (1961) . Numerous studies have since extended this analysis and shown that, as long as Ri is not too large, shear flows are unstable when there is a viscous-diffusive fluid (Howland et al, 2018), when there is preexisting ambient turbulence in the fluid (Kaminski & Smyth, 2019), or when the shear is unsteady (Radko, 2019…”
Section: Shear Mixingmentioning
confidence: 99%